1962
DOI: 10.1083/jcb.15.2.259
|View full text |Cite
|
Sign up to set email alerts
|

The Identification of Chylomicra and Lipoproteins in Tissue Sections and Their Passage Into Jejunal Lacteals

Abstract: The electron microscopic appearances of chylomicra and lipoproteins have been investigated. The particles were isolated from rat chyle by differential flotation in an ultracentrifuge. Various fixing and embedding media were used. The two kinds of particles were then identified in thin sections of the jejunum of rats. The chylomicra had diameters of from 1,000 A to 1 ~; the lipoproteins ranged from 100 to 1,000 A. They were identified by their sizes and their similarities to the isolated particles after the var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0
2

Year Published

1967
1967
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(46 citation statements)
references
References 29 publications
2
42
0
2
Order By: Relevance
“…In the core of the intestinal villus, it is generally considered that chylomicra enter into the central lacteal through the open gaps of endothelial junctions (CASLEY-SMITH, 1962;LADMAN et al, 1963;HORSTMANN and BREUKER, 1972), while DOBBINS and ROLLINS (1970) have suggested on the basis of their investigations using peroxidase, ferritin or chylomicron as a tracer that pinocytotic transport may also be very significant for chylomicron transport. The present study, however, is compatible with the opinion of CASLEY-SMITH and other workers.…”
Section: Discussionmentioning
confidence: 99%
“…In the core of the intestinal villus, it is generally considered that chylomicra enter into the central lacteal through the open gaps of endothelial junctions (CASLEY-SMITH, 1962;LADMAN et al, 1963;HORSTMANN and BREUKER, 1972), while DOBBINS and ROLLINS (1970) have suggested on the basis of their investigations using peroxidase, ferritin or chylomicron as a tracer that pinocytotic transport may also be very significant for chylomicron transport. The present study, however, is compatible with the opinion of CASLEY-SMITH and other workers.…”
Section: Discussionmentioning
confidence: 99%
“…The evidence which supports this belief is the almost complete disappearance of lipoprotein particles from fasting absorptive cells of rats (7) and men after biliary exclusion 8 and their absence from human jejunum after bile has been completely excluded by a short circuit operation for obesity. 9 The morphological evidence suggests that lipoprotein particles follow the same pathway in the fasting state as do chylomicrons and lipoprotein particles after a fatty meal. Lipoprotein particles were evident within endoplasmic reticulum, some of which connected with Golgi cisternae.…”
Section: Methodsmentioning
confidence: 99%
“…These particles were presumed to be lipoprotein because they were identical in appearance to those which Casley-Smith (9) found in the vicinity of rat intestinal lacteals and which he showed to be morphologically similar to those isolated from rat chyle by ultracentrifugation.…”
Section: Introductionmentioning
confidence: 99%
“…Lipid was observed to enter the lacteals through fenestrations in the endothelium, or across the endothelial cytoplasm (Casley-Smith, 1962). …”
Section: Extracellular Phasementioning
confidence: 99%
“…Particles similar to those isolated and identified as chylomicrons by Casley-Smith (1962) were prepared from intestinal lymph of a milk-fed calf and examined by electron microscopy ( Figure 33D). Size variation ranges from 90 to 360 mp, generally being larger than the apical or Golgi droplets observed in fixed tissue.…”
Section: Isolated Chylomicronsmentioning
confidence: 99%